A reinforcement material for soft tissue enhancement and its preparation method and application
By using fiber membrane structural reinforcement materials prepared by absorbable polymer materials and combined with elastic backing materials, the existing reinforcement materials have been solved, and the problems of insufficient adhesion and poor adaptability on the surface of human soft tissues have been achieved, which has achieved higher adhesion and adaptability, reducing the occurrence of surgical complications.
Patent Information
- Application Number
- CN202411993568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing reinforcement materials lack adhesion on the surface of human soft tissue, which can easily lead to anastomotic fistula and anastomotic stenosis, and have poor adaptability on different staplers and are prone to slip.
The fiber membrane is prepared by absorbable polymer materials, and the reinforcement material includes at least one fiber membrane structure. The glass transition temperature characteristics of the absorbable polymer are used to make the glass transition temperature of the fiber membrane close to the human body temperature, thereby improving adhesion. At the same time, elastic material is selected as the backing material to ensure that the patches are well adaptable to staplers of different structures and sizes.
The adhesion of the reinforcement material on the surface of the soft tissue of the human body is improved, the incidence of anastomotic fistula and stenosis is reduced, and the adaptability of the patch is enhanced, avoiding the problem of falling off the stapler.
Smart Images

Figure CN119746154A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a reinforcement material for soft tissue reinforcement, a preparation method and an application thereof. Background Art
[0002] In the modern medical field, when the human body's soft tissues show hyperplasia, lesions or necrosis, soft tissue resection surgery is usually used to remove the abnormal tissues to protect the patient's life and health. During this operation, the cut part needs to be anastomosed or sutured for reinforcement. The traditional reinforcement method usually uses excessive sutures, but it can still cause problems such as high anastomotic tension and poor anastomotic blood supply, leading to anastomotic fistula and anastomotic stenosis. According to existing literature: in laparoscopic gastric weight loss metabolic surgery, anastomotic fistula is the most common complication after gastric bypass surgery, with an incidence rate of 1.5%-5.5%, threatening the patient's life and health.
[0003] With the development of medical technology, the use of soft tissue reinforcement materials is currently considered an ideal solution. The principle is to apply a layer of sheet reinforcement material at the anastomosis or suture. After the operation, the reinforcement material will act between the staple line and the soft tissue to share the pressure of the staples, reduce the leakage rate, reduce inflammatory response, and compress hemostasis. This requires that the sheet reinforcement material not only needs to have good reinforcement properties, but also needs to have good tissue adhesion effect. The current common practice is to use fibrin glue or gel adhesive to improve the adhesion of sheet reinforcement materials, but this may cause foreign body reactions in tissues.
[0004] At the same time, when reinforcing the anastomosis, the sheet reinforcement material needs to be loaded on the stapler for use. Due to the design differences of the stapler structure, the adaptability of the product on different staplers may be inconsistent, resulting in the risk of slippage. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a reinforcing material with good adhesion for soft tissue enhancement and a medical patch based on the reinforcing material.
[0006] In order to achieve the above technical objectives, a technical solution of the present invention is:
[0007] A method for preparing a reinforcement material for soft tissue reinforcement, using at least one absorbable polymer material to prepare the reinforcement material for soft tissue reinforcement, the reinforcement material comprising at least one layer of fiber membrane structure, utilizing the glass transition temperature characteristics of the absorbable polymer to make the glass transition temperature of the fiber membrane close to the human body temperature, so as to improve the adhesion of the reinforcement material to the surface of human soft tissue.
[0008] Preferably, the absorbable polymer material is selected from one or more of polyglycolic acid, polyglycolide-trimethylene carbonate block copolymer, polyethylene glycol, polylactic acid, polycaprolactone, polyglycolide-lactide copolymer, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer. Preferably, each layer of fiber membrane is prepared by electrospinning process from at least one absorbable polymer material dissolved in the same solvent.
[0009] Preferably, each layer of fiber membrane is prepared from two or more absorbable polymer materials by a conjugated electrospinning process, and different absorbable polymer materials are dissolved in different solvents.
[0010] Preferably, the preparation methods of each layer of fiber membrane are the same or different.
[0011] Preferably, when the fiber membrane is made of one absorbable polymer material, the glass transition temperature of the absorbable polymer material should be 30-42°C; when the fiber membrane is made of two or more absorbable polymer materials, the glass transition temperature of at least one absorbable polymer material should be lower than 35°C, and the glass transition temperature of at least one absorbable polymer material should be higher than 40°C.
[0012] Preferably, the absorbable polymer material having a glass transition temperature of 30-42°C is selected from one of polyglycolic acid and polyglycolide-lactide copolymer, the absorbable polymer material having a glass transition temperature below 35°C is selected from one of polyethylene glycol, polycaprolactone, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer, and the absorbable polymer material having a glass transition temperature above 40°C is selected from one of polylactic acid and polyglycolide-trimethylene carbonate block copolymer.
[0013] Preferably, the glass transition temperature of at least one absorbable polymer material should be lower than 35°C, and the glass transition temperature of at least one absorbable polymer material should be higher than 40°C.
[0014] Preferably, the absorbable polymer material having a glass transition temperature lower than 35°C is selected from one of polyethylene glycol, polycaprolactone, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer, and the absorbable polymer material having a glass transition temperature higher than 40°C is selected from one of polylactic acid and polyglycolide-trimethylene carbonate block copolymer.
[0015] Preferably, when the fiber membrane is made of two or more absorbable polymer materials, at least one absorbable polymer material is recorded as material A, and the remaining absorbable polymer materials are recorded as material B. The mass ratio of material A to material B should meet the following conditions:
[0016] When (Tg A -37℃) / (37℃-Tg B )≥1, the mass of material A / the mass of material B = (0.6-2)×(Tg A -37℃) / (37℃-Tg B );
[0017] When (Tg A -37℃) / (37℃-Tg B )<1, the mass of material A / the mass of material B=(0.6-2)×(37℃-Tg B ) / (Tg A -37℃);
[0018] Among them, Tg A Indicates the glass transition temperature of material A, obtained by DSC characterization, Tg A Should be greater than 37℃, Tg B Indicates the glass transition temperature of material B, obtained by DSC characterization, Tg B Should be less than 37℃.
[0019] Preferably, when the fiber membrane is prepared by a conjugate electrospinning process, the ratio of the two absorbable polymer materials is adjusted by controlling the propulsion speed of the spinning solution or the concentration of the spinning solution.
[0020] As an improvement, when the reinforcement material is a fiber membrane structure with more than two layers, the glass transition temperature of a layer of fiber membrane used to adhere to human tissue should be 30-42°C, and the thickness of this layer should account for 30-80% of the overall fiber membrane.
[0021] The above technical solution has the following advantages:
[0022] The glass transition temperature characteristics of the absorbable polymer are utilized to make the glass transition temperature of the fiber membrane constituting the reinforcement material close to the human body temperature, thereby ultimately improving the adhesion of the reinforcement material to the surface of human soft tissue.
[0023] In order to achieve the above technical objectives, another technical solution of the present invention is:
[0024] A reinforcement material for soft tissue reinforcement is prepared using the above preparation method.
[0025] The above technical solution has the following advantages:
[0026] The glass transition temperature characteristics of the absorbable polymer are utilized to make the glass transition temperature of the fiber membrane constituting the reinforcement material close to the human body temperature, thereby ultimately improving the adhesion of the reinforcement material to the surface of human soft tissue.
[0027] To achieve the above technical objectives, the present invention also provides a medical patch, comprising the above reinforcement material for soft tissue enhancement and an elastic backing material, wherein the average Hooke's coefficient of the elastic backing material should be 500-1300 under a tensile deformation of 1 cm.
[0028] The above technical solution has the following advantages:
[0029] The glass transition temperature characteristics of the absorbable polymer are utilized to make the glass transition temperature of the fiber membrane that constitutes the reinforcement material close to the human body temperature, thereby ultimately improving the adhesion of the reinforcement material to the surface of human soft tissue; at the same time, an elastic material is selected as the backing material, so that when the patch is applied to the anastomosis device, it can adapt to anastomosis devices of different structures and sizes within a certain elastic range, thereby improving the adaptability of the patch and preventing the patch from falling off the anastomosis device. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the electron microscope image of the present invention;
[0031] Figure 2 This is a schematic diagram of a tubular patch product;
[0032] Figure 3 This is a structural diagram of the elastic backing material;
[0033] Figure numerals: 1. reinforcement material; 2. traction line; 3. backing material. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention in detail, but does not limit the claims of the present invention in any way.
[0035] In order to improve the adhesion of the reinforcement material used for soft tissue enhancement, the present invention utilizes the glass transition temperature characteristics of the absorbable polymer to make the glass transition temperature of the fiber membrane constituting the reinforcement material close to the human body temperature, thereby ultimately improving the adhesion of the reinforcement material to the surface of human soft tissue.
[0036] The specific method is as follows:
[0037] At least one absorbable polymer material is used to prepare a reinforcement material for soft tissue reinforcement, wherein the reinforcement material comprises at least one layer of fiber membrane structure;
[0038] in:
[0039] 1. The absorbable polymer material is selected from one or more of polyglycolic acid, polyglycolide-trimethylene carbonate block copolymer, polyethylene glycol, polylactic acid, polycaprolactone, polyglycolide-lactide copolymer, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer.
[0040] 2. Each layer of fiber membrane can be made of one absorbable polymer material; or can be made of two or more absorbable polymer materials.
[0041] (1) When the absorbable polymer material is prepared, the absorbable polymer material is prepared by an electrospinning process;
[0042] (2) When made of two or more absorbable polymer materials:
[0043] Various absorbable polymer materials can be dissolved in the same solvent and prepared by electrospinning process;
[0044] Various absorbable polymer materials can also be dissolved in different solvents and prepared by conjugated electrospinning process;
[0045] 3. When more than two layers of fiber membranes are included, the preparation methods of the fiber membranes of each layer may be completely the same, partially the same, or completely different.
[0046] 4. When more than two layers of fiber membranes are included, the total number of fiber membranes is preferably 2-4 layers, and the total thickness is preferably 100-250 microns.
[0047] 5. When the fiber membrane is made of an absorbable polymer material, the glass transition temperature of the absorbable polymer material should be 30°C-42°C, preferably 35-40°C, and optimally 37°C. In this case, the absorbable polymer material can be selected from polyglycolic acid and polyglycolide-lactide copolymer, preferably polyglycolic acid;
[0048] When the fiber membrane is prepared from two or more absorbable polymer materials, the glass transition temperature of at least one absorbable polymer material should be lower than 35°C, and the glass transition temperature of at least one absorbable polymer material should be higher than 40°C. Among them: the absorbable polymer material with a glass transition temperature lower than 35°C can be selected from polyethylene glycol, polycaprolactone, polylactide-caprolactone copolymer or polylactide-ethylene glycol block copolymer; the absorbable polymer material with a glass transition temperature higher than 40°C can be selected from polylactic acid and polyglycolide-trimethylene carbonate block copolymer.
[0049] 6. When the fiber membrane is made of more than two absorbable polymer materials, at least one absorbable polymer material is recorded as material A, and the remaining absorbable polymer materials are recorded as material B. The mass ratio of material A to material B should meet the following conditions:
[0050] When (Tg A -37℃) / (37℃-Tg B )≥1, the mass of material A / the mass of material B = (0.6-2)×(Tg A -37℃) / (37℃-TgB );
[0051] When (Tg A -37℃) / (37℃-Tg B )<1, the mass of material A / the mass of material B=(0.6-2)×(37℃-Tg B ) / (Tg A -37℃);
[0052] Among them, Tg A Indicates the glass transition temperature of material A, obtained by DSC characterization, Tg A Should be greater than 37℃, Tg B Indicates the glass transition temperature of material B, obtained by DSC characterization, Tg B Should be less than 37°C. DSC characterization method here:
[0053] (1) When material A or material B includes only one absorbable polymer material, the glass transition temperature of the material is Tg A Or Tg B ;
[0054] (2) When material A or material B includes more than two absorbable polymer materials, all absorbable polymer materials need to be dissolved and mixed by a solvent before being prepared into a fiber membrane. The fiber membrane is then subjected to a DSC test to measure the glass transition temperature of the fiber membrane. The glass transition temperature of the fiber membrane is Tg A or Tg B .
[0055] In addition, when prepared by conjugate electrospinning process, the proportion of absorbable polymer material can be adjusted to meet the above requirements by controlling the propulsion speed of the spinning solution or the concentration of the spinning solution. The specific method is as follows:
[0056] (1) When the propulsion speed of the spinning solution is used as the control variable:
[0057] The spinning liquid advancement speed ratio of material A and material B should meet the following conditions:
[0058] When (Tg A -37℃) / (37℃-Tg B )≥1, the spinning solution propulsion speed of material A / the spinning solution propulsion speed of material B=(0.6-2)×(Tg A -37℃) / (37℃-Tg B );
[0059] When (Tg A -37℃) / (37℃-Tg B)<1, the spinning solution propulsion speed of material A / the spinning solution propulsion speed of material B=(0.6-2)×(37℃-Tg B ) / (Tg A -37℃);
[0060] (2) When the concentration of the spinning solution is used as the control amount:
[0061] The spinning solution concentration ratio of material A and material B should meet the following conditions:
[0062] When (Tg A -37℃) / (37℃-Tg B )≥1, the spinning solution concentration of material A / the spinning solution concentration of material B = (0.6-2)×(Tg A -37℃) / (37℃-Tg B );
[0063] When (Tg A -37℃) / (37℃-Tg B )<1, the spinning solution concentration of material A / the spinning solution concentration of material B=(0.6-2)×(37℃-Tg B ) / (Tg A -37℃).
[0064] 8. When the reinforcement material is a fiber membrane structure with more than two layers, the glass transition temperature of a layer of fiber membrane used to attach to human tissue should be 30°C-42°C, preferably 35-40°C, and optimally 37°C; and the thickness of this layer should account for 30-80% of the entire fiber membrane, preferably 50-70%.
[0065] Based on the above preparation method, five specific examples of preparing reinforcement materials are provided below.
[0066] Example 1
[0067] This embodiment uses the following absorbable polymer material to prepare a reinforcement material for soft tissue enhancement with a single-layer fiber membrane structure.
[0068] Polyglycolic acid copolymer (Boli Bio, medical grade PGA-03, glass transition temperature measured at 39°C)
[0069] The specific steps are as follows:
[0070] 1. Prepare solution
[0071] A polyglycolic acid copolymer solution with a concentration of 12% and a dynamic viscosity of 800-1300 MPa.S was prepared using hexafluoroisopropanol as a solvent.
[0072] 2. Preparation of fiber membrane using electrospinning process
[0073] The prepared polyglycolic acid copolymer solution was used as the spinning solution for electrospinning to prepare a single-layer fiber membrane, wherein the electrospinning parameters were: voltage 28KV, spinning solution advancement speed 20ul / min, distance between the spinning nozzle and the receiver 18cm, ambient temperature and humidity 18-25°C and 50-70% respectively, and spinning time 120min.
[0074] Example 2
[0075] This embodiment uses the following two absorbable polymer materials to prepare a reinforcement material for soft tissue reinforcement having a single-layer fiber membrane structure.
[0076] Poly(glycolide-lactide) copolymer: Evonik, RESOMER GL903S (Tg measured at 32°C)
[0077] Polyglycolide-trimethylene carbonate block copolymer: Evonik, RESOMER GT643S (Tg measured at 59°C)
[0078] The specific steps are as follows:
[0079] 1. Prepare solution
[0080] A polyglycolide-lactide copolymer and a polyglycolide-trimethylene carbonate block copolymer solution with a dynamic viscosity of 800-1300 MPa.S was prepared using hexafluoroisopropanol as a solvent, wherein the concentration of the solution was 15%, and the mass ratio of polyglycolide-lactide to polyglycolide-trimethylene carbonate block copolymer was 4:1.
[0081] 2. Preparation of fiber membrane using electrospinning process
[0082] Electrospinning was carried out using the prepared polyglycolide-lactide copolymer and polyglycolide-trimethylene carbonate block copolymer solution as the spinning solution. The electrospinning parameters were: voltage 27 KV, spinning solution propulsion speed 30 ul / min, distance between the spinning nozzle and the receiver 30 cm, ambient temperature and humidity 18-25°C and 50-70% respectively, and spinning time 120 min.
[0083] Example 3
[0084] This embodiment uses the following two absorbable polymer materials to prepare a reinforcement material for soft tissue reinforcement having a two-layer fiber membrane structure.
[0085] Poly(glycolide-lactide) copolymer: Evonik, RESOMER GL903S (Tg measured at 32°C)
[0086] Polyglycolide-trimethylene carbonate block copolymer: Evonik, RESOMER GT643S (Tg measured at 59°C)
[0087] The specific steps are as follows:
[0088] 1. Prepare two solutions separately:
[0089] Using hexafluoroisopropanol as solvent, a polyglycolide-lactide copolymer solution with a concentration of 15% and a dynamic viscosity of 800-1300 MPa.S is prepared;
[0090] Using hexafluoroisopropanol as solvent, a polyglycolide-trimethylene carbonate block copolymer solution with a concentration of 15% and a dynamic viscosity of 600-900 MPa.S was prepared.
[0091] 2. The prepared polyglycolide-lactide copolymer solution was used as the spinning solution for electrospinning to prepare the first layer of fiber membrane, wherein the electrospinning parameters were: voltage 27KV, spinning solution propulsion speed 30ul / min, distance between the spinning nozzle and the receiver 30cm, ambient temperature and humidity 18-25℃ and 50-70% respectively, and spinning time 80min.
[0092] 3. Replace the spinning solution with the prepared polyglycolide-trimethylene carbonate block copolymer for electrospinning to prepare the second layer of fiber membrane, wherein the electrospinning parameters are: voltage 25KV, spinning solution propulsion speed 30ul / min, the distance between the spinning nozzle and the receiver is 25cm, the ambient temperature and humidity are 18-25℃ and 50-70%, and the spinning time is 40min. Thus, a double-layer fiber membrane is obtained.
[0093] Example 4
[0094] This embodiment uses the following three absorbable polymer materials to prepare a reinforcement material for soft tissue reinforcement having a two-layer fiber membrane structure.
[0095] Polyglycolide-lactide copolymer: Evonik, RESOMER Select 7525 (Tg measured at 53°C) Polylactide-caprolactone copolymer: Evonik, RESOMER LC703S (Tg measured at 29°C)
[0096] Polylactide-ethylene glycol block copolymer, Jinan Jufukai Biotechnology, MPEG5000-PLA5000, (Tg measured value is 13℃)
[0097] The specific steps are as follows:
[0098] 1. Prepare two solutions separately:
[0099] Using hexafluoroisopropanol as solvent, a solution with a concentration of 15% polyglycolide-lactide copolymer and polylactide-caprolactone copolymer (wherein the mass ratio of polyglycolide-lactide copolymer to polylactide-caprolactone copolymer is 4:1) and a dynamic viscosity of 800-1300 MPa.S is prepared;
[0100] Using dichloromethane as solvent, a polylactide-ethylene glycol block copolymer solution with a concentration of 15% and a dynamic viscosity of 1000-1500 MPa.S was prepared.
[0101] 2. The prepared mixed solution of polyglycolide-lactide copolymer and polylactide-caprolactone copolymer was used as the spinning solution for electrospinning to prepare the first layer of fiber membrane, wherein the electrospinning parameters were: voltage 25KV, spinning solution propulsion speed 25ul / min, distance between spinning nozzle and receiver 28cm, ambient temperature and humidity 18-25℃ and 50-70% respectively, and spinning time 80min.
[0102] 3. Replace the spinning solution with the prepared polylactide-ethylene glycol block copolymer solution for electrospinning to prepare the second layer of fiber membrane, wherein the electrospinning parameters are: voltage 20KV, spinning solution propulsion speed 25ul / min, the distance between the spinning nozzle and the receiver is 25cm, the ambient temperature and humidity are 18-25℃ and 50-70%, and the spinning time is 40min. Thus, a double-layer fiber membrane is obtained.
[0103] Example 5
[0104] This embodiment adopts two absorbable polymer materials and utilizes a conjugate electrospinning process to prepare a reinforcement material for soft tissue reinforcement having a single-layer fiber membrane structure.
[0105] The specific steps are as follows:
[0106] Polyglycolide-lactide copolymer: Evonik, RESOMER Select 7525 (Tg measured at 53°C) Polylactide-caprolactone copolymer: Evonik, RESOMER LC703S (Tg measured at 29°C)
[0107] 1. Prepare two solutions separately:
[0108] Using dimethylformamide as solvent, a solution with a concentration of 15% polyglycolide-lactide copolymer and a dynamic viscosity of 800-1300 MPa.S is prepared;
[0109] Using hexafluoroisopropanol as solvent, a solution of polylactide-caprolactone copolymer with a concentration of 15% and a dynamic viscosity of 600-1200 MPa.S is prepared;
[0110] 2. The prepared polyglycolide-lactide copolymer and polylactide-caprolactone copolymer were subjected to conjugate electrospinning, wherein the parameters for the polyglycolide-lactide copolymer spinning were: voltage 25KV, spinning solution propulsion speed 30ul / min, the distance between the spinning nozzle and the receiver was 20cm, the ambient temperature and humidity were 18-25℃ and 50-70%, and the spinning time was 60min. The parameters for the polylactide-caprolactone copolymer spinning were: voltage 28KV, spinning solution propulsion speed 17ul / min, the distance between the spinning nozzle and the receiver was 25cm, the ambient temperature and humidity were 18-25℃ and 50-70%, and the spinning time was 60min.
[0111] In the specific implementation of the present invention, when a multi-nozzle array spinning of multiple polymer materials is adopted, the array interval of the spinning nozzles of different materials is preferably 1 to 3.
[0112] The performance of the reinforcement materials prepared in the above five embodiments was tested, and the results are shown in Table 1:
[0113] Table 1
[0114] project Example 1 Example 2 Example 3 Example 4 Example 5 DSC Testing 38.4℃ 34.2℃ 35.6℃ 39.2℃ 35.1℃
[0115] In Table 1: The conditions of the DSC test are: set the gas flow rate to 50 mL / min, the initial temperature to -30°C, set the heating program to 20°C / min, heat to 80°C, and set the cooling program to 20°C / min, cool to -30°C.
[0116] It can be seen from the above table that the glass transition temperature of the reinforcement material for soft tissue reinforcement prepared by the present invention is in the range of 30-42°C. When the glass transition temperature of the reinforcement material for soft tissue reinforcement is close to the human body temperature, the polymer molecular chains constituting the reinforcement material begin to thaw and transform from a glassy state to a highly elastic state. The material itself tends to be soft, which is conducive to the adhesion effect between the material and the tissue. The adhesion performance is significantly better than that of existing reinforcement materials. Figure 1 Shown is an electron microscope image of the reinforcement material for soft tissue enhancement prepared by the present invention.
[0117] The application of the above reinforcement materials is described below.
[0118] Medical patches can be made based on the reinforcement material prepared above and combined with the backing material. However, when the patch is used to reinforce the anastomosis, the patch product needs to be loaded on the stapler for use. Due to the design differences of stapler structures of different brands and specifications, the patch product needs to have better adaptability. Therefore, the elastic material is innovatively selected as the backing material, so that the patch product can adapt to staplers of different structures and sizes within a certain elastic range to prevent the patch from falling off the stapler.
[0119] In order to find a backing material with suitable elastic properties and simulate the application scenario of the stapler, the present invention provides a method for testing the elasticity of the backing material:
[0120] Method 1: Cut the elastic backing material into 1×5cm strips, set the distance between the universal testing machine clamps to 1cm, stretch at a speed of 200mm / min, stop stretching when the distance between the clamps rises by 1cm, and test the force value at this time.
[0121] Method 2: Sewing the elastic backing material and the reinforcing material composed of fiber membrane into Figure 2 For the tubular patch product shown, the tubular patch product is respectively put on cylinders with a diameter of 1 cm and a diameter of 2 cm to simulate the loading form when the product is used, and then the force required to remove the tubular product from the cylinder is tested by a universal testing machine. Specifically, the lower fixture of the universal testing machine is used to hold the cylinder, and the upper fixture is used to clamp the tubular product. The product is stretched at a speed of 200 mm / min until it falls off the cylinder, and the maximum force is recorded.
[0122] The above test method was used to test a variety of common elastic backing materials. The specific results are shown in Table 2:
[0123] Table 2
[0124] Material Nylon-spandex elastic knitted fabric Nylon-spandex elastic knitted fabric Nylon-spandex elastic knitted fabric Specification 7010D 70140D 70210D Method 1 test results 4.99N 12.30N 23.32N Method 2 (1CM cylinder) test results 3.26N 5.37N 9.24N Method 2 (2CM cylinder) test results 12.41N 20.47N 34.27
[0125] From the above table, it can be seen that when the average Hooke's coefficient of the 1cm backing material is between 500-2300 when stretched by 1cm, the removal force is between 12.41-20.47N according to the test results of method 2. Since too large a removal force will affect the efficiency of loading the stapler on the tubular product, it is preferred to use an elastic material with an average Hooke's coefficient of 500-1300 under a tensile deformation of 1cm. For example: nylon-spandex elastic knitted fabric (specification model 7010D to 70140D). Figure 3 The above selection is only part of the selection test results of the present invention. The present invention does not exclude the selection of other backing materials that meet the elasticity requirements. When the present invention is implemented, other types of backing materials that meet the elasticity requirements can be selected according to the application.
[0126] In summary, the present invention has the following advantages:
[0127] 1. The glass transition temperature characteristics of absorbable polymers are used to make the glass transition temperature of the fiber membrane constituting the reinforcement material close to the human body temperature, thereby ultimately improving the adhesion of the reinforcement material to the surface of human soft tissue.
[0128] 2. Select elastic material as the backing material so that when the patch is applied to the stapler, it can adapt to staplers of different structures and sizes within a certain elastic range, thereby improving the adaptability of the patch and preventing the patch from falling off the stapler.
Claims
1. A method for preparing a reinforcement material for soft tissue enhancement, characterized in that: At least one absorbable polymer material is used to prepare a reinforcement material for soft tissue reinforcement. The reinforcement material includes at least one layer of fiber membrane structure. The glass transition temperature characteristics of the absorbable polymer are utilized to make the glass transition temperature of the fiber membrane close to the human body temperature, so as to improve the adhesion of the reinforcement material to the surface of human soft tissue.
2. The method for preparing a reinforcement material for soft tissue enhancement according to claim 1, characterized in that: The absorbable polymer material is selected from one or more of polyglycolic acid, polyglycolide-trimethylene carbonate block copolymer, polyethylene glycol, polylactic acid, polycaprolactone, polyglycolide-lactide copolymer, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer.
3. The method for preparing a reinforcement material for soft tissue enhancement according to claim 1, characterized in that: Each layer of fiber membrane is prepared by an electrospinning process using at least one absorbable polymer material dissolved in the same solvent.
4. The method for preparing a reinforcement material for soft tissue enhancement according to claim 1, characterized in that: Each layer of fiber membrane is prepared from more than two absorbable polymer materials through a conjugated electrospinning process, and different absorbable polymer materials are dissolved in different solvents.
5. The method for preparing a reinforcement material for soft tissue enhancement according to claim 1, characterized in that: The preparation methods of each layer of fiber membrane are the same or different.
6. The method for preparing a reinforcement material for soft tissue enhancement according to claim 3, characterized in that: When the fiber membrane is made of an absorbable polymer material, the glass transition temperature of the absorbable polymer material should be 30-42°C; When the fiber membrane is made of two or more absorbable polymer materials, the glass transition temperature of at least one absorbable polymer material should be lower than 35°C, and the glass transition temperature of at least one absorbable polymer material should be higher than 40°C.
7. The method for preparing a reinforcement material for soft tissue enhancement according to claim 6, characterized in that: The absorbable polymer material with a glass transition temperature of 30-42°C is selected from one of polyglycolic acid and polyglycolide-lactide copolymer, the absorbable polymer material with a glass transition temperature below 35°C is selected from one of polyethylene glycol, polycaprolactone, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer, and the absorbable polymer material with a glass transition temperature above 40°C is selected from one of polylactic acid and polyglycolide-trimethylene carbonate block copolymer.
8. The method for preparing a reinforcement material for soft tissue enhancement according to claim 4, characterized in that: The glass transition temperature of at least one absorbable polymer material should be below 35°C and the glass transition temperature of at least one absorbable polymer material should be above 40°C.
9. The method for preparing a reinforcement material for soft tissue enhancement according to claim 8, characterized in that: The absorbable polymer material having a glass transition temperature lower than 35°C is selected from one of polyethylene glycol, polycaprolactone, polylactide-caprolactone copolymer and polylactide-ethylene glycol block copolymer, and the absorbable polymer material having a glass transition temperature higher than 40°C is selected from one of polylactic acid and polyglycolide-trimethylene carbonate block copolymer.
10. The method for preparing a reinforcement material for soft tissue enhancement according to claim 3 or 4, characterized in that: When the fiber membrane is made of two or more absorbable polymer materials, at least one absorbable polymer material is recorded as material A, and the remaining absorbable polymer materials are recorded as material B. The mass ratio of material A to material B should meet the following conditions: When (Tg A -37℃) / (37℃-Tg B )≥1, the mass of material A / the mass of material B = (0.6-2)×(Tg A -37℃) / (37℃-Tg B ); When (Tg A -37℃) / (37℃-Tg B )<1, the mass of material A / the mass of material B=(0.6-2)×(37℃-Tg B ) / (Tg A -37℃); Among them, Tg A Indicates the glass transition temperature of material A, obtained by DSC characterization, Tg A Should be greater than 37℃, Tg B Indicates the glass transition temperature of material B, obtained by DSC characterization, Tg B Should be less than 37℃.
11. The method for preparing a reinforcement material for soft tissue enhancement according to claim 10, characterized in that: When the fiber membrane is prepared by a conjugate electrospinning process, the ratio of the two absorbable polymer materials is adjusted by controlling the propulsion speed of the spinning solution or the concentration of the spinning solution.
12. The method for preparing a reinforcement material for soft tissue enhancement according to claim 1, characterized in that: When the reinforcement material is a fiber membrane structure with more than two layers, the glass transition temperature of a layer of fiber membrane used for attaching human tissue should be 30-42° C., and the thickness of this layer should account for 30-80% of the entire fiber membrane.
13. A reinforcement material for soft tissue reinforcement, characterized in that: The method is used to prepare the product according to any one of claims 1 to 9.
14. A medical patch, characterized in that: It comprises the reinforcement material for soft tissue enhancement as claimed in claim 13 and an elastic backing material, wherein the average Hooke's coefficient of the elastic backing material under a tensile deformation of 1 cm should be 500-1300.